G328(P) A UK-wide review of deaths in children and young people with epilepsies. (7th April 2014) - Sidebotham, P; Hunter, L
Abstract : Objective: To review cases of mortality in 1–18 year olds with epilepsies, in order to identify and learn from clinical and organisational management or personal issues that contributed to adverse outcomes so as to inform clinical practice and improve clinical services for children across the UK. Methods: Over a 10 month period case notifications were collected from consultant paediatricians across the UK. These included cases of 1–18 year olds with a diagnosis of epilepsy who died (of any cause). For all eligible cases a clinical questionnaire was sent to the notifying clinician. Cases of mortality were included in a more detailed case note review. Case notes were reviewed by pairs of paediatricians and nurses using a purpose-built assessment tool, derived from national guidelines. Results: In total 46 valid clinical questionnaires were collected. Case notes were obtained and a detailed case notes review carried out in 33 children. Over half the children who died did so of causes other than their epilepsy, predominantly from existing co-morbidities (24/46 cases; 52%); 7 (15%) children died as a consequence of status epilepticus, and 7(15%) from SUDEP. 43 (93%) children who died had co-existing disability, leading to multiple professionals being involved in the child's care. Eight (24%) deaths were deemed to have been preventable; the main identified factors related to fragmentation of care; support for families in responding to emergencies; and hospital responses to the acutely unwell child, including those presenting with status epilepticus. Conclusions: The findings of the review highlight the need for a lead clinician to coordinate the child's care. This clinician should communicate the risks of prolonged seizure and Sudden Unexpected Death in Epilepsy to parents and carers. After a child dies a review should take place to identify modifiable factors and learn lessons to prevent future deaths. Support and advice for the family shouldn't end after a child dies and this information should be documented in the child's notes.